Intrinsic Innervation of the Persian Squirrel (Sciurus anomalus) Ileum. (4th September 2012) - Sadeghinezhad, J.; Tootian, Z.; Latorre, R.; Sorteni, C.; Chiocchetti, R.
Summary Most investigations related to the characterisation of the enteric nervous system (ENS) are pivoted on the intestine of small rodents, but few studies are available on the ENS of wild or 'unconventional' rodents. Anti‐PGP 9.5 and anti‐Hu antibodies were utilised to recognise the distribution pattern of neuronal cell bodies and fibres of the ileum of the Persian squirrel (Sciurus anomalus) ENS. The percentages of subclasses of enteric neurones in the total neuronal population were investigated by neuronal nitric oxide synthase (nNOS), choline acetyltransferase (ChAT), calcitonin gene‐related peptide (CGRP), substance P (SP), and calbindin (CALB). Myenteric plexus (MP) and submucosal plexus (SMP) neurones showing nNOS immunoreactivity (IR) were 41 ± 4% and 11 ± 6%, respectively, whereas cells expressing ChAT‐IR were 56 ± 9% and 74 ± 16%, respectively. nNOS‐IR was co‐expressed by 21 ± 2% and 9 ± 4% of the MP and SMP cholinergic neurones, respectively, whereas the nNOS‐IR MP and SMP neurones co‐expressing ChAT‐IR were 86 ± 6% and 89 ± 2%, respectively. CGRP‐IR and SP‐IR were expressed, respectively, by 13 ± 5% and 6 ± 3% of MP and 18 ± 2% and 2 ± 2% of SMP neurones. CALB‐IR was expressed by 22 ± 8% and 56 ± 14% of MP and SMP neurones, respectively. MP and SMP cholinergic neurones co‐expressed nNOS‐IR (21 ± 2% and 9 ± 4%, respectively) and a very high percentage of nNOS‐IR neurones showed ChAT‐IR (86 ± 6% and 89 ± 2%, respectively). MP and SMP CALB‐IR neurones co‐expressed ChAT‐IR (100% and 63 ± 11%, respectively) and CGRP‐IR (89 ± 5% and 26 ± 7%, respectively). Our data might contribute to the neuroanatomical knowledge of the gastrointestinal tract in exotic mammals and provide a comparison with the available data on other mammals.